The Aggregate Gradation in Road Reconstruction - Hakzah, Hakzah; Andriansyah, Andriansyah; Mustakim, Mustakim; Jasman, Jasman (Universitas Ibn Khaldun Bogor, 2024)
Reconstruction of the road section uses the flexible pavement method where aggregate material is the main component of the structure. Choosing the right aggregate gradation and meeting the specification requirements will greatly determine the quality of the road. This research aims to determine the characteristics of aggregate gradation sourced from stock files and compare the results of aggregate gradation analysis of job mix design planning consultants. The method uses laboratory testing. Aggregate wear test results 2-3 = 5.36%, 1-2 = 6.14%. The absorption value of aggregate 2-3 = 0.87%, 1-2 = 1.79%, 0.5 - 1 = 1.80% and stone ash = 2.27%. Values of dry specific gravity, SSD specific gravity, and apparent specific gravity of aggregate 2-3 = 2.73, 2.69, 2.66, 1-2 = 2.72, 2.64, 2.62 0.5- 1 = 2.70, 2.62, 2.58, rock ash = 2, 53, 2.59, 2.69. These values meet the requirements of the 2018 Bina Marga specifications, 2nd revision. The comparison of the results of the field aggregate gradation test analysis with the results of the job mix design analysis is the same because the aggregates tested come from the same stock file. The results of the sieve analysis test showed that the coarse aggregate fineness modulus of 2-3, 1-2, and 0.5 - 1 did not meet the specification standards, while the fine aggregate for stone ash did. The value that does not meet is caused by not paying attention to the additional note that the coarse aggregate retained on the 1